Impact of reduce tide from different tidal station to bathymetric survey using [multibeam] in Terengganu / Mohamad Imannudin Azman - Azman, Mohamad Imannudin (2018)
Tide is very important component in bathymetry survey, this is because tide were used in bathymetry data processing to product the actual depth of the survey area. Inaccurate tidal data will end up with inaccurate water depth which is will effect the purpose of the survey. This project aim to study the impact of different reduce tide from different tidal station to a multibeam survey data which is based on the distance of the tidal station. The bathymetry data involved in this project were taken at Bidong Island, Terengganu which is under University Malaysia Terengganu (UMT) in cooperation with THSGeoscience company. This research consisted of tide observation data which is collect by automatic tide gauge at Bidong Island while survey conducted, and two other tide prediction which is generated by using harmonic constant of Chendering and Kuala Dungun tide station. Both selected tide station were chosen differently based on it distance to the survey area. These tide data were load into the same bathymetry separately in order to know the effect. From the result of the research, it is can be see that there was slight surface different between observation tide data to prediction tide data and there is not much different for both prediction data though it has different distance to the survey area. It is hope that this study will create an alert to the importance of tide station selection regarding to it distance from bathymetry survey area.